2021
DOI: 10.2147/copd.s281957
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Management and In-Hospital Clinical Outcomes Among Inpatients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in China: Results from the Phase I Data of ACURE Study

Abstract: Purpose The study aimed to give a comprehensive overview of characteristics and evaluate in-hospital clinical outcomes among hospitalized acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients in China using data from the AECOPD inpatient registry (ACURE). Patients and Methods The ACURE is an ongoing, national, multicenter, observational registry. Participants enrolled during phase I stage (1 st September 2017 to 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Although the efforts to teach CS and establish patient-centered communication have shown promising results [ 8 ], this approach is not common practice in Chinese clinical settings [ 28 , 29 ]. Tertiary-care hospitals seem to be faring better in clinical aspects [ 30 , 31 ] but a national framework for medical professionalism among Chinese physicians is yet to be enforced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the efforts to teach CS and establish patient-centered communication have shown promising results [ 8 ], this approach is not common practice in Chinese clinical settings [ 28 , 29 ]. Tertiary-care hospitals seem to be faring better in clinical aspects [ 30 , 31 ] but a national framework for medical professionalism among Chinese physicians is yet to be enforced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that clinical management of COPD during the stable period was unsatisfactory in China in another analysis of ACURE database. 13 Therefore, it needs to strengthen management of COPD in the stable stage needs to be popularized and strengthened, which could then delay the decline of lung function and reduce acute exacerbation of COPD. Third, PHD treatment is mainly to maintain lung function and oxygen therapy, which has remained almost unchanged for the past 3 decades.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the data collection have been described in previously published paper. 13 According to the 2017 Global Initiative for Chronic Obstructive Lung Disease (GOLD), the severity of airflow limitation was classified into four grades: GOLD 1 (forced expiratory volume in the first second, FEV 1 % predicted ≥ 80), GOLD 2 (50 ≤ FEV 1 % predicted < 80), GOLD 3 (30 ≤ FEV 1 % predicted < 50), and GOLD 4 (FEV 1 % predicted < 30). ECG and echocardiography were performed during the hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…The ACURE study was started on September 1, 2017 and planned to recruit 7,600 hospitalized patients with AECOPD who were admitted to 161 participating medical centers across China with a maximum of 3-year follow-up. The protocol of the ACURE registry and baseline characteristics of the study population have been published (31,32).…”
Section: Study Design and Settingsmentioning
confidence: 99%